Do economic, institutional or political variables explain regulated wholesale unbundled local loop rate setting? - Madden, Gary; Dippon, C.; Suenaga, Hiroaki (Routledge, 2016)
This study examines OECD fully unbundled and line-sharing monthly wholesale prices for 2002–2008. Although both series are well explained by the models, the principal contribution of the research is that economic, institutional and political factors explain mandated wholesale rate settings. The study finds evidence of both regulatory capture (to benefit incumbents) and retail margin setting to encourage entry (to benefit entrants).